Pengembangan Modul Pembelajaran Teks Prosedur Berbantuan Komik Digital pada Siswa Kelas X di SMA Mamiyai Al-Ittihadiyah - Dalimunthe, Nafi Tri Amirah; Ali, Ali; Amaluddin, Amaluddin (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2025)
This study aims to develop and evaluate the feasibility and effectiveness of a digital comic-assisted procedural text learning module for 10th-grade students at SMA Mamiyai Al-Ittihadiyah. Employing the Research and Development (R&D) approach using the 4D model—define, design, develop, and disseminate—the study systematically assessed the module's impact. The findings indicate that the developed module was rated as "Highly Feasible" by media experts (87.34% and 89.34%) and content experts (69% and 70%). Field trials demonstrated the module’s effectiveness, with students' learning outcomes improving to a "Highly Effective" level, achieving a success rate of 92%. These results suggest that digital comic-based learning modules significantly enhance students' engagement and comprehension of procedural texts. The integration of interactive digital media in learning materials fosters greater student motivation and deeper understanding, reinforcing the potential of technology-assisted education in secondary schools.